Global Asthma Network Survey Suggests More National Asthma Strategies Could Reduce Burden of Asthma - Mallol-Villablanca, E (Elsevier Doyma, 2017)
Background Several countries or regions within countries have an effective national asthma strategy resulting in a reduction of the large burden of asthma to individuals and society. There has been no systematic appraisal of the extent of national asthma strategies in the world. Methods The Global Asthma Network (GAN) undertook an email survey of 276 Principal Investigators of GAN centres in 120 countries, in 2013–2014. One of the questions was: “Has a national asthma strategy been developed in your country for the next five years? For children? For adults?”. Results Investigators in 112 (93.3%) countries answered this question. Of these, 26 (23.2%) reported having a national asthma strategy for children and 24 (21.4%) for adults; 22 (19.6%) countries had a strategy for both children and adults; 28 (25%) had a strategy for at least one age group. In countries with a high prevalence of current wheeze, strategies were significantly more common than in low prevalence countries (11/13 (85%) and 7/31 (22.6%) respectively, p < 0.001). Interpretation In 25% countries a national asthma strategy was reported. A large reduction in the global burden of asthma could be potentially achieved if more countries had an effective asthma strategy. © 2017 SEICAP